Odpowiedzi

2010-02-21T18:39:29+01:00
A)
6(x+y)=10y
y-x=0,5
6x+6y=10y
y=0,5+x
6x+0,5+x=(0,5+x)10
y=0,5+x
7x+0,5=5+10x
y=0,5+x
-3x=4,5
y=0,5+x
x=-1,5
y=0,5+x
x=-1,5
y=-1
b)
10(y+2)+3(x-5)=x-5
25(y+2)+3(x-5)=-10
10y+20+3x-15=x-5
25y+50+3x-15=-10
10y+2x=-10
25y+3x=25
2x=-10-10y
25y+3x=25
x=-5-5y
25y+3x=25
x=-5-5y
25y+3(-5-5y)=25
x=-5-5y
25y-15-15y=25
x=-5-5y
10y=40
x=-5-5y
y=4
x=-5-20
y=4
x=-15
y=4
c)
2(2x-y)+3(x+3y)=42
5(x+3y)-8(2x-y)=-32
4x-2y+3x+9y=42
5x+15y-16x+8y=-32
7x+7y=42 |:7
23y-11x=-32
x+y=6
23y-11x=-32
x=6-y
23y-11x=-32
x=6-y
23y-11(6-y)=-32
x=6-y
23y-66+11y=-32
x=6-y
34y=34
x=6-y
y=1
x=5
y=1

Oczywiście wszystko bierzesz w klamerki po bokach. ;p
1 5 1
2010-02-21T18:53:34+01:00
A) 6(x + y) = 10y
y - x = 0,5
6(x + y) = 10y
y = 0,5 + x
6(x + 0,5 + x) = 10(0,5 + x)
y = 0,5 + x
6x + 3 + x = 5 + 10x
y = 0,5 + x
-3x = 2 /(-3)
y = 0,5 + x
x = -⅔
y = 0,5 - ⅔
x = -⅔
y = ½ - ⅔
x = -⅔
y = -⅙

b) 2(2x-y)+3(x+3y)=42
5(x+3y)-8(2x-y)=-32
4x-2y+3x+6y=42
5x+15y-16x+8y=-32
7x=42-4y /7
5x+15y-16x+8y=-32
x=7-⁴/₇y
5(7-⁴/₇y)+15y-16(7-⁴/₇y)+8y=-32
x=7-⁴/₇y
35-²⁰/₇y+15y-112+⁶⁴/₇y+8y=-32
x=7-⁴/₇y
35y=-32 /35
x=7-⁴/₇y
y=-³²/₃₅
x=7-⁴/₇(-³²/₃₅)
y=-³²/₃₅
x=7+¹²⁸/₂₄₅
y=-³²/₃₅